Influence Of Taxpayer Moral Strength, Tax Authority Power, And Tax Sanctions On Taxpayer Compliance - Pebriansyah, Yoda; Irwansyah, Irwansyah (Jurnal Ekonomi, 2024)
This study uses the SmartPLS method to analyze the effect of taxpayer moral strength, tax authority strength, and tax sanctions on taxpayer compliance at the Bengkulu Primary Tax Office. Respondents as many as 109 taxpayers were the subject of the study. The results showed that the moral strength of taxpayers and the strength of the tax authority have a significant positive effect on taxpayer compliance. This means that the stronger the morale of taxpayers and tax authorities, the higher the level of taxpayer compliance in the region. However, interesting results emerged in the tax sanction independence variable, which turned out to have a significant negative effect on taxpayer compliance. This finding indicates that the more independent the tax sanctions, the lower the level of taxpayer compliance. The results of this study are expected to make a significant contribution to the understanding of the factors that influence taxpayer compliance